Numerical Investigation of Seepage and Heat Transfer in Rocks with Various Fracture Patterns for Geothermal Energy Extraction. (5th July 2022) - Yang, Zhaoying; Wang, Jun; Long, Xiting; Wang, Xuan
Abstract : Unraveling the seepage and heat transfer coupled process between the working fluid and the fractured rocks in geothermal reservoir is of great significance to the exploitation and utilization of geothermal resources. In this study, based on the numerical modeling of fracture flow in geothermal reservoirs, the seepage and convective heat transfer behavior of fractured granite during geothermal extraction were investigated, and the effects of different fracture patterns, fluid injection temperature, and injection velocity on the temperature evolution of rock mass were comparatively analyzed. The results clearly revealed the influence of five different fracture patterns, i.e., single fracture, echelon fracture, parallel fracture, Y-shaped fracture, and crossfracture, on heat transfer capacity. Generally, the echelon fracture has the highest fluid outlet temperature, while the crossfracture has the largest total heat and shows the strongest heat transfer capacity. Besides the fracture shape, the fluid injection temperature and injection velocity also play significant roles in the heat transfer performance. The increase of fluid injection temperature would improve the total outlet heat of the crossfracture system and also benefit the system life. When the fluid injection temperature raises from 20°C to 35°C, the system life and the total outlet heat would be increased by 58.76% and 22.42%, respectively. However, higher fluid injection velocity would damage the system life of the geothermal reservoir, which obviously results in a decrease in total outlet heat. With the fluid injection velocity increasing from 0.004 m/s to 0.006 m/s, the system life could drop by 72.47%, and the total outlet heat was reduced by 55.72%. This work contributes to the preliminary understanding of the coupled seepage and heat transfer behavior in rock mass with various fracture patterns, and it could provide some practical implications for the rational exploitation of geothermal resources.